Eight hours for what we will: workers and leisure in an industrial city, 1870-1920 - Rosenzweig, Roy (Interdisciplinary Perspectives on Modern History, 1985)
Rosenzweig asked us to analyze labor through its counterpoint - leisure. Using statistics, public statements, and secondary sources Rosenzweig uses a Birmingham School look at the Worcester working class. Rosenzweig explores not in opposition but more curious about the ´alternative´ cultures. The question he asks is, How does leisure change in Worcester over time? The insights are attached to the book´s finale by the suggestions that the contest over the use of leisure became an arena of class struggle, with the reader being cautioned not to be deceived into thinking that Worcester was a city without class conflicts (Rosenzweig, Eight Hours for What We Will 225). In the first broad study of American working-class recreation, Rosenzweig takes us to the saloons, the ethnic and church picnics, the parks and playgrounds, the amusement parks, and the movie houses where industrial workers spent their leisure hours. Centering on the city of Worcester, Massachusetts, he illustrates the deep transformation that popular leisure underwent. Explaining what these pastimes and amusements tell us about the nature of working-class culture and class relations in this era, Rosenzweig articulates that in order fully to comprehend the working class experience it is indispensable to investigate the realm of leisure. For what workers did in the corner saloon, the neighborhood park, the fraternal lodge hall, the amusement park, and the nickelodeon had a good deal of bearing on what happened inside the factories, the union halls, and the voting booths of America´s industrial communities.